Electrical bending instability in electrospinning visco‐elastic solutions. Issue 11 (15th March 2016) - Shariatpanahi, S. Peyman; Bonn, Daniel; Ejtehadi, Mohammad R.; Zad, Azam Iraji
ABSTRACT: The electrical bending instability in charged liquid jets is the phenomenon determining the process of electrospinning. A model of this phenomenon is lacking however, mostly due to the complicated interplay between the viscosity and elasticity of the solution. To investigate the bending instability, we performed electrospinning experiments with a solution of polyethylene oxide in water/ethanol. Using a fast camera and sensitive multimeter, we deduced an experimental dispersion relation describing the helix pitch length as a function of surface charge. To understand this relation, we developed a theoretical model for the instability for a wide range of visco‐elastic materials, from conducting to nonconducting. The theoretical dispersion relation shows good agreement with the experimental results. Using the new model, we find that the elastic tension in the visco‐elastic threads plays an important role in triggering the instability. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1036–1042 Abstract : Electrospinning is a well known method for polymeric micro and nano fibers synthesis. Bending instability, as the key phenomenon in the method, is investigated theoretically and experimentally for visco‐elastic solutions. It is shown that the initial elastic tension stored in the jet before instability plays a significant role in the process. The theory contributes to a much better understanding and control of electrospinning using different materials.